Analysis of Weight Faltering among Toddlers in Jakarta in 2025 - Paryanti, Nanik Paryanti; Rukmaini; Putri Azzahroh (Rajaki of Tulip Medika Publisher, 2026)
Weight Faltering in toddlers is an early indicator of nutritional status disorders that can impact a child's growth and development. This condition reflects an imbalance between nutritional intake, metabolic needs, and infectious disease factors. In Indonesia, cases of Weight Faltering in toddlers are still quite high and are a concern in efforts to improve toddler nutrition, including in the Jakarta area. The objective was to analyze factors related to the incidence of Weight Faltering in toddlers. These factors included a history of exclusive breastfeeding, dietary patterns, history of infectious diseases, and immunization history. The study used a quantitative descriptive correlational design with a cross-sectional approach. The study population was 87 toddlers in the Jakarta area, using a total sampling technique. Data were collected through weight measurements, interviews using questionnaires, 24-hour dietary recall forms, and searches of KIA books. Data analysis was performed using univariate and bivariate methods. The results of the bivariate analysis showed that dietary patterns (p = 0.002) and history of infectious diseases (p = <0.001) had a significant relationship with the incidence of Weight Faltering in toddlers. Toddlers with poor diets and a history of infectious diseases are at higher risk of experiencing poor Weight Faltering . Weight Faltering in toddlers is influenced by diet and a history of infectious diseases. A history of exclusive breastfeeding and immunizations are not directly related to the incidence of poor or stable weight faltering.